Text-to-braille translator - Nuratikah Asyikin, Jamaludin (2019)
Braille is a form of written language for visually impaired people, in which characters are represented by patterns of raised dots that are felt with the fingertips. The discerning person can not usually read Braille information without training. Therefore, many parents have difficulty in educating their blind children. Next, teachers that are engaged in special education have to depend on Braille translator when marking Braille papers or assignments. Therefore, this system proposed are aiming to help the people who have zero knowledge in Braille code to learn the code. This system will also have better prospects for application, shorten the time taken to translate and provide assistance to the beginners in learning Braille characters.